Clinical and Economic Outcomes of Intradiscal Injection of Condoliase for a Treatment of Lumbar Disc Herniation with Severe Low Back Pain: A Multicenter Study - Takashi Hirai; Takuya Takahashi; Yohei Takahashi; Kota Watanabe; Tomohiro Banno; Kyohei Sakaki; Yoshiyasu Arai; Yuichi Takano; Yawara Eguchi; Yuki Taniguchi; Satoshi Maki; Yasuchika Aoki; et al. (Spine Surgery and Related Research)
Introduction: Chemonucleolysis with condoliase (chondroitin sulfate ABC endolyase) has been widely employed to treat patients with lumbar disc herniation (LDH) in Japan. Although it is an effective and relatively safe treatment for radicular neuropathy in patients with LDH, there have been no reports that investigate how severe low back pain (LBP) changes after condoliase injection. In this multicenter study, the effectiveness of condoliase injection for reducing severe LBP in patients with LDH was evaluated. Methods: This retrospective study involved patients treated with intradiscal condoliase injection for LDH at nine participating centers. Patients were diagnosed with subligamentous-type herniation based on pretreatment MRI. Patients with severe LBP (defined as a preinjection numeric rating scale [NRS] for LBP greater than or equal to that for leg pain) were categorized into the LBP group. Demographic data, adverse events, treatment costs, and the NRS for LBP and lower extremity pain were analyzed. A 50% response was defined as 50% improvement in the NRS at 1 year postinjection. On the basis of the Pfirman classification, the LBP group was divided into less-degenerative (Grades II and III) and degenerative (Grades IV and V) subgroups. Results: Seventy-nine patients were classified into the LBP group. Of these patients, 61 (77.2%) showed a >50% reduction in LBP, and another 61 (77.2%) demonstrated a >50% reduction in lower extremity pain. Improvement of lower limb pain was considerably better in the less-degenerative group than in the degenerative group, whereas that of low back pain was similar between the two subgroups. Medical costs, which include remuneration for injection, drug fees, inpatient costs, and other expenses, were similar between the LBP group and all cases. Conclusions: This retrospective multicenter study revealed that patients with LDH with severe LBP frequently experienced improvement in radicular pain and LBP, which is similar to LDH cases without severe LBP.